Long-Term Effects of Severe Burns on the Kidneys: Research Advances and Potential Therapeutic Approaches - Yang G; Tan L; Yao H; Xiong Z; Wu J; Huang X (Dove Medical Press, 2023)
Guang Yang,1,2,* Lishan Tan,1,* Hua Yao,3 Zuying Xiong,1 Jun Wu,4,5 Xiaoyan Huang1 1Division of Renal Medicine, Peking University Shenzhen Hospital, Peking University, Shenzhen, 518000, People's Republic of China; 2Department of Life Sciences, Yuncheng University, Yuncheng, 044006, People's Republic of China; 3Guangxi Key Laboratory of Brain and Cognitive Neuroscience, Guilin Medical College, Guilin, 541004, People's Republic of China; 4Department of Burn and Plastic Surgery, Shenzhen Institute of Translational Medicine, Shenzhen Second People's Hospital, the First Affiliated Hospital of Shenzhen University, Shenzhen, 518035, People's Republic of China; 5Human Histology & Embryology Section, Department of Surgery, Dentistry, Pediatrics & Gynecology, University of Verona Medical School, Verona, Venetia, 37134, Italy*These authors contributed equally to this workCorrespondence: Xiaoyan Huang; Jun Wu, Email huangxiaoyan@pku.org.cn; junwupro@126.comAbstract: Burns are a seriously underestimated form of trauma that not only damage the skin system but also cause various complications, such as acute kidney injury (AKI). Recent clinical studies have shown that the proportion of chronic kidney diseases (CKD) in burn patients after discharge is significantly higher than that in the general population, but the mechanism behind this is controversial. The traditional view is that CKD is associated with hypoperfusion, AKI, sepsis, and drugs administered in the early stages of burns. However, recent studies have shown that burns can cause long-term immune dysfunction, which is a high-risk factor for CKD. This suggests that burns affect the kidneys more than previously recognized. In other words, severe burns are not only an acute injury but also a chronic disease. Neglecting to study long-term kidney function in burn patients also results in a lack of preventive and therapeutic methods being developed. Furthermore, stem cells and their exosomes have shown excellent comprehensive therapeutic properties in the prevention and treatment of CKD, making them increasingly the focus of research attention. Their engineering strategy further improved the therapeutic performance. This review will focus on the research advances in burns on the development of CKD, illustrating the possible mechanism of burn-induced CKD and introducing potential biological treatment options and their engineering strategies.Keywords: inflammation, acute kidney injury, chronic kidney diseases, stem cells, exosomes, sepsis, cytokine storm